TESTING THE ANTIBACTERIAL ACTIVITY OF MORINGA LEAF (Moringa oleifera L.) ETHANOL EXTRACT ON THE GROWTH OF THE BACTERIA Propionibacterium acnes IN VITRO - Nisrina Afiqah Rahmi; Ahmad Shafwan S. Pulungan (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2024)
ABSTRACTThis study aims to determine the antibacterial activity of ethanol extract of Moringa oleifera L. leaves against the growth of Propionibacterium acnes bacteria in vitro and to determine the active compounds contained in the ethanol extract of Moringa oleifera L. leaves. This research is experimental and the method used is disc diffusion, namely by observing, measuring, calculating and analyzing the diameter of the growth inhibition zone of P. acnes which forms around the disc containing ethanol extract of Moringa leaves. The results of antibacterial activity show that the ethanol extract of Moringa oleifera L. leaves has antibacterial activity against the growth of Propionibacterium acnes bacteria and the active compounds contained in the ethanol extract of Moringa oleifera L. leaves which were tested using the phytochemical screening method, namely tannin and saponin compounds, and flavonoids.Keywords: Ethanol, Moringa leaves, antibacterial, Propionibacterium acnes.